Penyuluhan kesehatan penyakit menular seksual (PMS) pada remaja - Keswara, Umi Romayati; Mardani, Mardani; Nepiana, Nurul; Triyono, Taufiq Hidayat; Rita, Desi Risna; Palupi, Antika (Indonesian Public Health-Observer Information Forum (IPHORR) Kerja sama dengan: Unit Penelitian dan Pengabdian Kep Akademi Keperawatan Baitul Hikmah, 2024)
Background: Adolescence is a transition period from childhood to adulthood, where rapid growth occurs including reproductive function that affects changes in development, both physical, mental, and social roles. Today's youth association needs to be highlighted especially, because currently the association of adolescents is very worrying due to the development of the global modernization current and the depletion of one's morals and faith. The association of adolescents today is very worrying, namely the high rate of drug use among adolescents, and the existence of free sex among adolescents outside marriage. Purpose: To increase adolescents' knowledge and understanding of sexually transmitted disease behaviour. Method: The implementation of this activity goes through several stages, namely conducting field surveys, holding cadus meetings to explain about health extension activity technicians, providing media that will be used for counseling in the form of poster media. Results: Adolescents were asked to understand the importance of avoiding sexually transmitted diseases, and an assessment of the process in the form of questions and answers given by the speaker was carried out until all participants could understand the importance of avoiding sexually transmitted diseases. Conclusion: The participants in hamlet 06 sukajaya lempasing Bandar Lampung City knew about knowledge of sexually transmitted diseases. Keywords: Adolescence; Health Education; Sexually Transmitted Diseases. Pendahuluan: Masa remaja adalah masa transisi dari masa kanak-kanak ke dewasa, di mana terjadi pertumbuhan yang cepat termasuk fungsi reproduksi yang mempengaruhi perubahan perkembangan, baik peran fisik, mental, maupun sosial. Pergaulan remaja saat ini perlu disoroti terutama, karena saat ini pergaulan remaja sangat mengkhawatirkan akibat perkembangan arus modernisasi yang mendunia dan menipisnya akhlak dan iman seseorang. Pergaulan remaja saat ini sangat mengkhawatirkan, yaitu tingginya angka penggunaan narkoba di kalangan remaja, dan adanya seks bebas di kalangan remaja di luar nikah. Tujuan: Untuk menambah pengetahuan dan pemahaman remaja tentang perilaku penyakit menular seksual. Metode: Pelaksanaan kegiatan ini melalui beberapa tahapan yaitu melakukan survey lapangan, mengadakan pertemuan pihak kadus untuk menjelaskan tentang teknisi kegiatan penyuluhan kesehatan, menyediakan media yang akan digunakan untuk penyuluhan berupa media poster. Hasil: Remaja diminta untuk memahami pentingnya menghindari penyakit menular seksual, serta dilakukan penilaian proses berupa tanya jawab yang diberikan pemateri tersebut sampai semua peserta bisa memahami pentingnya menghindari penyakit menular seksual. Simpulan: Para peserta di Dusun 06 Sukajaya Lempasing Kota Bandar Lampung mengetahui tentang pengetahuan penyakit menular seksual.